2020
DOI: 10.18632/oncotarget.27608
|View full text |Cite
|
Sign up to set email alerts
|

Amplifications of stemness genes and the capacity of breast tumors for metastasis

Abstract: Introduction:The phenomenon of non-CSC (cancer stem cell) to CSC plasticity has been previously described in multiple studies and occurs during the ectopic expression of stemness genes such as OCT3, SOX2, KLF4, MYC, NOTCH1, and NANOG.In our opinion, acquiring the ability to ectopically express stemness genes, selected by bioinformatics analysis and, accordingly, non-CSC to CSC plasticity, is due to amplification of genes at the following locations: 3q, 5p, 6p, 7q, 8q, 13q, 9p, 9q, 10p, 10q21.1, 16p, 18chr, 19p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 32 publications
0
20
0
2
Order By: Relevance
“…It was found that in cases when tumor cell clones with 2 or more amplifications of the above chromosomal regions remained in a residual tumor after neoadjuvant chemotherapy, 50 % of the patients developed metastases. When all amplifications were eliminated or only one amplification remained, 100 % of patients did not develop metastases [1]. The results of this study showed that the presence of 2 or more amplifications at regions of stemness gene localization in residual tumors was a necessary, but not sufficient condition for metastasis development.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…It was found that in cases when tumor cell clones with 2 or more amplifications of the above chromosomal regions remained in a residual tumor after neoadjuvant chemotherapy, 50 % of the patients developed metastases. When all amplifications were eliminated or only one amplification remained, 100 % of patients did not develop metastases [1]. The results of this study showed that the presence of 2 or more amplifications at regions of stemness gene localization in residual tumors was a necessary, but not sufficient condition for metastasis development.…”
Section: Introductionmentioning
confidence: 73%
“…Thus, our data indicate that CNA genes of WNTsignaling are associated with metastasis and the prognostic value of CNA genes of WNT-signaling in residual tumors is highly predictive, which confirms our working hypothesis that CNA genes of WNT signaling are involved in the implementation of the metastasis process. Amplifications of stemness genes give tumor cells the ability to do stem transition [1], amplifications of activators SKP1, WNT8A, MAPK9, CCND3, FZD9, WNT8B, CCND1, PLCB2, PRKCB, FZD2, WNT3, WNT9B and / or deletions of negative regulators of WNT signaling genes: GSK3B, APC, CSNK2B, SFRP5, BTRC, TCF7L2, CSNK2A2, contribute to the release of tumor cells from replicative aging and dormant state, and activation of stem transition.…”
Section: Laboratory and Experimental Studiesmentioning
confidence: 99%
“…In HCC-1599 cells, both ATRA-and DAPTdependent down-regulation of the NOTCH1 pathway causes a substantial reduction in the expression levels of MYC and the MYC-dependent network. In this cell-line, the concordant anti-MYC action of ATRA and DAPT may be one of the major mechanisms underlying the anti-tumour action of the two compounds, as MYC is a well-known regulator of cancer cell stemness (50). Interestingly down-regulation of the MYC pathway is enhanced by the combination of ATRA + DAPT, which suggests that the two compounds exert complementary anti-MYC effects.…”
Section: Discussionmentioning
confidence: 79%
“…In HCC-1599 cells, both ATRA- and DAPT-dependent down-regulation of the NOTCH1 pathway causes a substantial reduction in the expression levels of MYC and the MYC-dependent network. In this cell line, the concordant anti-MYC action of ATRA and DAPT may be one of the major mechanisms underlying the anti-tumor action of the two compounds, as MYC is a well-known regulator of cancer cell stemness [ 46 ]. Interestingly, down-regulation of the MYC pathway is enhanced by the combination of ATRA+DAPT, which suggests that the two compounds exert complementary anti-MYC effects.…”
Section: Discussionmentioning
confidence: 99%